2005
DOI: 10.1007/s00586-005-0012-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of intra-abdominal pressure in the unloading and stabilization of the human spine during static lifting tasks

Abstract: The unloading and stabilizing actions of IAP, hence, appear to be posture and task specific.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 71 publications
6
39
0
1
Order By: Relevance
“…Indirect effect of the transverse abdominal and latissimus dorsi muscles in unloading the spine through lumbodorsal fascia have been reported not being sizable during lifting tasks [11,15,61,65,70,95]. Moreover, the likely mechanical effects of the intra-abdominal pressure (IAP), neglected in this study, have been found to depend on the posture and the co-activity level of abdominal muscles [7]. While local muscles were modeled as straight lines between their respective insertion points, realistic muscle paths were considered for global extensor muscles by wrapping them over all T12-S1 vertebrae whenever in the course of lifts their distance to associated vertebral bodies reduced more than 10% of their initial distances.…”
Section: Methodological Issuesmentioning
confidence: 70%
“…Indirect effect of the transverse abdominal and latissimus dorsi muscles in unloading the spine through lumbodorsal fascia have been reported not being sizable during lifting tasks [11,15,61,65,70,95]. Moreover, the likely mechanical effects of the intra-abdominal pressure (IAP), neglected in this study, have been found to depend on the posture and the co-activity level of abdominal muscles [7]. While local muscles were modeled as straight lines between their respective insertion points, realistic muscle paths were considered for global extensor muscles by wrapping them over all T12-S1 vertebrae whenever in the course of lifts their distance to associated vertebral bodies reduced more than 10% of their initial distances.…”
Section: Methodological Issuesmentioning
confidence: 70%
“…As remarked before, both the ribcage 43,51 and intra-abdominal pressure [52][53][54][55][56] have a large effect on the stability and stiffness of the spine. However, the effect of neither of these have ever been analysed in adolescents.…”
Section: Aim and Outline Of This Thesismentioning
confidence: 67%
“…As no specific mechanism is proven right or wrong yet, all these effects should be considered when modelling the IAP. However, currently, the IAP is often modelled as a single force on the middle of the diaphragm [52][53][54] . This is most likely an oversimplification of the biomechanical function, since two effects are neglected in this way of modelling: both the increased stiffness of the abdominal muscles and the physiological function of the IAP in maintaining the shape of these muscles and the direct effects of the IAP on limiting the movement of the spinal column are neglected.…”
Section: Intra-abdominal Pressurementioning
confidence: 99%
“…Five lumbar intervertebral joints (L1-L2 through L5-S1) were modeled as custom joints, each with three rotational and three translational DOFs. A constant force representing intra-abdominal pressure (IAP) was applied between the pelvis and the torso (4 cm anterior to the T12 level) [20]. The force in each static posture (Table 1) was based on in vivo measurements of IAP [21], assuming a 200 cm 2 abdominal cross-sectional area [20] and linear variation with flexion angle [22].…”
Section: Musculoskeletal Modelmentioning
confidence: 99%